Function of the RNA-binding activity of the nuclear mRNA-binding protein Npl3 in nuclear mRNA packaging - Keil, Philipp; Justus Liebig University Giessen (My University, 2021)
An essential step of gene expression is the formation of a messenger ribonucleoprotein particle (mRNP). Already during transcription the nascent mRNA is bound by mRNA-binding proteins (RBPs) that package the mRNA into an mRNP. The formation of mRNPs is crucial for mRNA stability and only correctly packaged mRNPs are exported from the nucleus through the nuclear pore complexes to the cytoplasm. The nuclear export of mature mRNPs is mediated by the mRNA export receptor Mex67-Mtr2, which is mainly recruited by adaptor proteins like the RNA-annealing protein Yra1, the poly(A)-binding protein Nab2, and the SR-like protein Npl3. Besides nuclear events, bound RBPs often regulate cytoplasmic events such as localization, translation and degradation of the mRNA. The functions of the proteins involved in these processes have largely been analyzed by depletion or deletion of either the whole protein or entire protein domains, which will often abrogate multiple activities of each protein at once. To determine specifically the functional significance of the RNA-binding activity of proteins involved in nuclear mRNP formation, we identified the amino acids that are in close proximity to RNA by UV-light crosslinking and subsequent mass spectrometric analyses. Approximately 100 amino acids that could be crosslinked to RNA in vivo were identified in various proteins involved in mRNP formation, namely in Npl3, Nab2, Tho1, Mex67-Mtr2 and in most components of the TREX complex (Tho2, Hpr1, Mft1, Hrb1, Sub2 and Yra1). To selectively disrupt the interaction of RNA with the newly identified putative binding sites, selected amino acids that crosslinked to RNA were mutated and afterwards the RNA-binding activity was analyzed. After confirmation of reduced RNA-binding activity, the functional consequences of these mutations on mRNP assembly, mRNA export, mRNA expression and stability, and splicing were then analyzed in detail. In this study, we carried out mutational analysis of the protein Npl3. Npl3 is an SR-like protein involved in transcription, 3’ end formation, mRNP assembly and nuclear mRNA export. Npl3 contains two RRM domains connected by a non-structured flexible linker, an SR/RGG motif at its C-terminus and an APQE motif in its N-terminus. Three npl3 mutants were generated, one in the linker-region and one within each of the two RRM domains, and the functional consequences of these mutations were elucidated. Interestingly, reduction of mRNA-binding in the three different regions of Npl3 had different phenotypic outcomes, suggesting that the different functional activities of the protein are independent from each other. Moreover, analysis of the npl3-Linker mutant revealed a novel function of Npl3. Npl3 acts as an initial factor in the transfer of nuclear mRNP components to the mRNA. In sum, putative in vivo RNA binding sites of nuclear mRNA binding proteins were identified. In addition, disruption of verified RNA binding sites in different regions of Npl3 has specific and surprisingly different functional consequences. Furthermore, a novel function of Npl3 in nuclear mRNP assembly was discovered.
Keywords: Npl3; mRNA packaging; RNA-binding protein (RBP); ddc:500; ddc:570